Sudden loss of vision - N. du Toit (South African Family Practice)
Sudden loss of vision, which causes consternation for both the patient and clinician, is a clinical problem that is encountered fairly regularly in most primary healthcare settings. Sudden visual loss or obscuration which is transient may simply be a symptom of a dry eye or a migraine, but it may also be the onset of irreversible visual loss or a stroke. Most cases of sudden loss of vision are serious, require referral and have an associated underlying systemic disease. Visual loss is usually unilateral, but may be bilateral. This clinical problem may present a diagnostic challenge. No cause may be found in some instances. However, it is important to remember that the more sinister causes of sudden visual loss, such as temporal arteritis, carotid or cardiac emboli that cause retinal vascular occlusion, retinal detachment, vitreous haemorrhage and orbital masses, need to be identified early. Using the duration of the visual loss as the primary differentiating factor, with associated symptoms and signs as supplementary factors, the causes can be narrowed down. A thorough history, goal-directed examination, proper investigation and appropriate referral should enable early diagnosis and adequate management. This will prevent further ocular morbidity, and even patient mortality.